Transjugular intrahepatic portosystemic shunt is associated with significant changes in mitral inflow parameters - Pudil, Radek; Praus, Rudolf; Hulek, Petr; Safka, Vaclav; Fejfar, Tomas; Vasatova, Martina; Jirkovsky, Vaclav (Annals of hepatology, 2013)
INTRODUCTION: Liver cirrhosis is associated with hyperdynamic circulation which can result in heart failure. Transjugular intrahepatic portosystemic shunt (TIPS) due to increase of cardiac output is a stressful stimulus for cardiovascular system. Therefore, new methods for early detection of heart failure are needed. Transmitral flow is a marker of diastolic dysfunction. AIM: To analyze short- and long-term effect of TIPS procedure on transmitral flow. MATERIAL AND METHODS: 55 patients (38 men and 17 women, 55.6 ± 8.9 years) with liver cirrhosis treated with TIPS were enrolled in the study. Echocardiography was performed before, 24 h, 7, 30 and 180 days after the procedure. During 6 month follow up 22 patients died. Results. Left ventricle end-diastolic diameter was increasing during the follow-up [baseline: 47 (44.7-51.2) mm, day 7: 50 (46.5-51.3) mm, p < 0.05; day 30: 49.5 (46.7-55.2) mm, p < 0.01; 6 months: 52.5 (48.3-55.2) mm, p < 0.01)]. The peak early filling velocity (E) was significantly increasing [before: 75.5 (60.5-87.3) cm/s, 24 h: 88 (74.3-109.7), p < 0.01; day 7: 89 (81.5-105) p < 0.01; 1 month: 94 (82.7-108.5) p < 0.01; 6 month: 91 (80.1-120.2) p < 0.01]. Peak late atrial filling velocity (A) significantly increased within 24 h after the procedure: 85.1 (76.2-99.5) vs. 91.2 (81.5-104.5) cm/s, p < 0.05. The E/A ratio was increasing during the follow up (baseline: 0.88, 24 h after: 0.89, 1 week: 1.0, 30 days: 1.13, 6 month: 1.06 p < 0.01). CONCLUSION: Hemodynamic changes following TIPS procedure can be monitored using echocardiography. Transmitral flow analysis can serve as a useful tool for evaluating of diastolic function in these patients.
Keywords: Stroke Volume; dospělí; Echocardiography, Doppler, Color; Kaplan-Meier Estimate; Chi-Square Distribution; Female; transjugulární intrahepatální portosystémový zkrat; Liver Cirrhosis; Adult; ženské pohlaví; Kaplanův-Meierův odhad; Heart Failure; Predictive Value of Tests; Hemodynamics; hemodynamika; jaterní cirhóza; prediktivní hodnota testů; časové faktory; funkce levé komory srdeční; lidé; srdeční selhání; Time Factors; Male; Aged; tepový objem; Mitral Valve; rozdělení chí kvadrát; mitrální chlopeň; barevná dopplerovská echokardiografie; lidé středního věku; senioři; mužské pohlaví; Portasystemic Shunt, Transjugular Intrahepatic; Middle Aged; Ventricular Function, Left; Humans